From Industry 5.0 to 6.0: Future Skills for Human–Technology Collaboration in Sustainable Manufacturing - Joanna OLEŚKÓW-SZŁAPKA (Communications of International Proceedings, 2025)
The transition from Industry 4.0 through Industry 5.0 toward Industry 6.0 marks a paradigmatic shift from technology-driven automation to sustainable, human–machine symbiosis. While Industry 4.0 emphasized digitalization, cyber–physical systems, and data integration, Industry 5.0 reintroduced human-centricity, sustainability, and resilience as key pillars of industrial transformation. Building on this foundation, Industry 6.0 envisions hyper-connected, autonomous, and adaptive ecosystems where humans and intelligent systems co-evolve within ethically governed and environmentally conscious frameworks. This paper explores how the principles of Industry 5.0 form the conceptual and operational basis for Industry 6.0 and identifies the evolving skill sets necessary for future workforce adaptability. Using a multidisciplinary approach combining conceptual synthesis and review of recent empirical studies, the paper examines emerging competences required to navigate technological complexity and sustainability imperatives. Findings indicate that technical proficiencies—such as artificial intelligence, quantum computing, and data analytics—must be complemented by meta-skills including adaptability, creativity, ethical reasoning, and systems thinking. The study concludes that successful transition to Industry 6.0 requires more than technological readiness—it demands a holistic alignment between innovation, human capital development, and systemic sustainability. Preparing engineers and managers for this new paradigm calls for curricula integrating digital literacy with social, environmental, and ethical dimensions, enabling them to act as mediators between technological progress and sustainable societal transformation.
Keywords: Industry 6.0; Industry 5.0; Industry 4.0; Future skills; Sustainability and Resilience; Workforce transformation; Transdisciplinary Innovation; Hyperconnectivity